Reading Comprehension in Children With Specific Language Impairment: An Exploratory Study of Linguistic and Decoding Skills - Coloma, Carmen Julia; Silva, Macarena; Palma, Sandra; Holtheuer, Carolina (Psykhe, 2015)
The present study explored the relationship between linguistic and decoding skills in children with specific language impairment (SLI), inquiring whether reading comprehension is associated with linguistic or decoding skills in these children. Non-probability sampling was used. The sample consisted of 19 first grade Chilean students from 6 middlelow socioeconomic status schools in Santiago, Chile. They were 6 years old on average: 10 children with SLI (7 male) and 9 who displayed typical development (6 male). Participants were assessed on linguistic measures (mean length of utterance [MLU] and narrative), decoding, and reading comprehension. Descriptive analyses showed that the children with SLI exhibited difficulties in reading comprehension and decoding. Using Fisher’s exact test, it was found that the children with SLI and low reading comprehension performed more poorly than the control group in narrative comprehension, narrative production, and MLU. This association was not observed between reading comprehension and decoding skills. The results suggest that linguistic abilities play a major role in the reading comprehension of children with SLI.